Rowley Reconsidered: The (Re)Constitution of Free Appropriate Public Education through Multiple Possible Discourses - Susan Baglieri (Disability Studies Quarterly, 2006)
In this response to Rosen's article, "An unintended consequence of IDEA," I expand his argument to consider the multiple possible ways that everyday people interpret the law as practice. The dominance of the law arises in an interdependent relationship between the intent of the law-writers as expressed in text and the public discourses in which disability and education gain meaning. I present the 1982 case of the Board of Education v. Rowley as a backdrop to examine discourses in disability and education that may have informed the Supreme Court's ruling on "Free Appropriate Public Education," and further offer understanding into the school context that led to litigation at the outset. Finally, I propose the central roles of teachers, whose changes in classroom discourses are at the heart of the increasing prominence of Deaf culture and ASL in schools.
Keywords: IDEA; Deaf Studies; Inclusion; Disability Studies